Agreement Between Bioelectrical Impedance Analysis and Ultrasound for Measuring Body Composition in Women with Breast Cancer - Jared Rosenberg; Jyotsna Natarajan; David J. Carpenter; Chris Peluso; Christie Hilton; Colin E. Champ (Diagnostics)
Background/Objectives: Higher percent body fat (BF) is associated with worse outcomes after treatment for breast cancer (BC). While ultrasound (US) imaging is a reliable method for analyzing body composition, it requires trained individuals for utilization. As such, bioelectrical impedance analysis (BIA) has been suggested as an alternative. Therefore, the goal of this study was to compare BIA with US. Methods: Women from three prospective exercise BC studies were analyzed with US and BIA before an exercise intervention. Spearman’s correlation was used as a nonparametric measure to examine bivariate relationships between percent body fat measured by BIA and US. Results: In total, 106 women with BC had their body composition measured using both US and BIA. Despite a strong correlation between the two methods (r = 0.8, p < 0.01), US reported lower mean percent BF vs. BIA (34.6 ± 0.7% vs. 38.0 ± 0.8%, p < 0.01). In a subgroup analysis, concordance was seen in women with a body mass index below (BMI) ≤ 26 kg/m2. BIA overreported percent BF compared to US in women with a BMI > 26 kg/m2. Conclusions: In women with BC and BMI ≤ 26, US and BIA are in concordance when measuring BF. In women with a BMI > 26, BIA reports a higher BF than US. Overall, there was a strong correlation between modalities, while BMI can be used to guide the utilization of BIA as an alternative to US for assessing body composition.